2023
DOI: 10.1002/jgm.3508
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transcriptome, proteome and single‐cell sequencing uncover the prognostic and immunological features of colony‐stimulating factor 3 receptor in pan‐cancer

Abstract: BackgroundColony‐stimulating factor 3 receptor (CSF3R) has been demonstrated to be associated with various hematological tumors, especially chronic neutrophilic leukemia; however, the detailed roles of CSF3R in other cancers remain to be explored.MethodsIn the present study, we systematically analyzed the expression profiles of CSF3R in pan‐cancer by comprehensive bioinformatics databases, such as Tumor Immune Estimation Resource, version 2 (TIMER2.0), Gene Expression Profiling Interactive Analysis, version 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…Moreso, its expression was positively correlated with the tumor infiltration of cancer-associated fibroblasts and dendritic cells. CSF3R was found to be associated with cancer-associated pathways, and further studies could determine whether CSF3R methylation values can be used as a prognostic marker [56]. A closely related gene, CSF1R, had previously shown prognostic value by association with poor outcome when overexpressed through hypomethylation [57].…”
Section: Dna Methylation As a Biomarkermentioning
confidence: 98%
See 1 more Smart Citation
“…Moreso, its expression was positively correlated with the tumor infiltration of cancer-associated fibroblasts and dendritic cells. CSF3R was found to be associated with cancer-associated pathways, and further studies could determine whether CSF3R methylation values can be used as a prognostic marker [56]. A closely related gene, CSF1R, had previously shown prognostic value by association with poor outcome when overexpressed through hypomethylation [57].…”
Section: Dna Methylation As a Biomarkermentioning
confidence: 98%
“…Another pan-cancer TCGA-based study found that colony-stimulating factor 3 receptor (CSF3R) is up-regulated in TGCT, and its promoter's methylation level was found to be lower in non-seminomas compared with seminomas [56]. Moreso, its expression was positively correlated with the tumor infiltration of cancer-associated fibroblasts and dendritic cells.…”
Section: Dna Methylation As a Biomarkermentioning
confidence: 99%
“…Generally, TB is classified based on several criteria including clinical features, pathological presentations, Mycobacterium tuberculosis drug resistance, and molecular epidemiology 6 . Clinically, it can be divided into primary and secondary forms, while pathologically, it may manifest as caseous, infiltrative, or fibrotic TB.…”
Section: Introductionmentioning
confidence: 99%
“…The immune environment plays a critical role in the development of TB, influencing how the disease progresses 11 . After infection, the tuberculosis bacteria cause lung inflammation and immune cell buildup, creating an environment that promotes inflammation 6 , 12 , 13 . However, the bacteria also manipulate the immune response, making it harder for the body to clear them.…”
Section: Introductionmentioning
confidence: 99%